Absurdity of Human Condition: A Study of Fritz Karinthy's Refund (Sukuna Journal, 2026)
Fritz Karinthy’s one-act drama Refund effectively presents the absurd condition of human life through the comic yet striking idea of an adult demanding reimbursement for his schooling. This study attempts to find out the absurdist traits of the drama that are connected to the broader literary scenario of Samuel Beckett, Eugène Ionesco, and Albert Camus. In Refund, Karinthy makes a harsh critique of human stupidity and follies of the educational system using illogical conditions, irrational behaviours, and ironic twists. In fact, Absurdism, philosophically speaking, tries to delve into the conflict between our continuous search for meaning within meaninglessness. An absurdist approach emphasizes how literary texts explore meaninglessness, irrationality, and the breakdown of logical sequence. It talks about how characters face and react to purposeless and disordered circumstances in the text. Some main features of Absurdism can be the lack of obvious reasoning and a vain attempt to find a sense in connection to the play. Karinthy creates such a dramatic world in which logic does not function, and the educational institution presents itself in an illogical manner. The student’s responses have been manipulated, and ignorance has been rewarded over knowledge in Refund. Therefore, Karinthy’s Refund shows bureaucratic illogicality, revealing comic absurdity as rigid rules produce irrational outcomes in our education system.